Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.4049/jimmunol.0902436
|View full text |Cite
|
Sign up to set email alerts
|

Arginase II Restricts Host Defense to Helicobacter pylori by Attenuating Inducible Nitric Oxide Synthase Translation in Macrophages

Abstract: Helicobacter pylori infection of the stomach causes peptic ulcer disease and gastric cancer. Despite eliciting a vigorous immune response, the bacterium persists for the life of the host. An important antimicrobial mechanism is the production of NO derived from inducible NO synthase (iNOS). We have reported that macrophages can kill H. pylori in vitro by an NO-dependent mechanism, but supraphysiologic levels of the iNOS substrate l-arginine are required. Because H. pylori induces arginase activity in macrophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
101
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(109 citation statements)
references
References 58 publications
7
101
0
Order By: Relevance
“…In H. pylori-stimulated macrophages, iNOS protein translation is dependent on the level of L-Arg in culture medium and bacterial killing requires high levels of L-Arg (46). Consistent with this, increased iNOS translation and NO production occurred with inhibition of arginase or siRNA knockdown of Arg2 or in primary macrophages from Arg2 Ϫ/Ϫ mice, while oral administration of an arginase inhibitor to H. pylori-infected mice increased iNOS protein expression and NO production by gastric macrophages (174). Second, Arg2 has a central role in inducing apoptosis of macrophages, which is dependent on the metabolism of its product, L-ornithine, into polyamines (116).…”
Section: General Considerations For Innate and Adaptive Immunitysupporting
confidence: 53%
“…In H. pylori-stimulated macrophages, iNOS protein translation is dependent on the level of L-Arg in culture medium and bacterial killing requires high levels of L-Arg (46). Consistent with this, increased iNOS translation and NO production occurred with inhibition of arginase or siRNA knockdown of Arg2 or in primary macrophages from Arg2 Ϫ/Ϫ mice, while oral administration of an arginase inhibitor to H. pylori-infected mice increased iNOS protein expression and NO production by gastric macrophages (174). Second, Arg2 has a central role in inducing apoptosis of macrophages, which is dependent on the metabolism of its product, L-ornithine, into polyamines (116).…”
Section: General Considerations For Innate and Adaptive Immunitysupporting
confidence: 53%
“…In the present study, increased arginase activity in VL was found to be associated with upregulation of arginase 1 enzyme at both the mRNA and protein level. Though mitochondrial arginase 2 expression could restrict macrophage NO production in Helicobacter pylori infection [30], we have excluded the role of arginase 2 in increasing arginase activity as arginase 2 was not induced in L. donovani-infected mice.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies macrophages were also activated with live H. pylori SS1 at an MOI of 10 (2, 34). C. rodentium was grown, and lysates were prepared as described (35). C. jejuni was obtained from ATCC, and lysates were prepared as for H. pylori.…”
Section: Methodsmentioning
confidence: 99%
“…C57BL/6 mice were inoculated by oral gavage with 5 ϫ 10 8 colony-forming units of H. pylori in 0.1 ml of Brucella broth or broth vehicle control. For the colonization time points of 14, 60, and 120 days, the mice were gavaged every other day three times (7,36), whereas for the time points of 1-7 days, the mice were inoculated once (35). In some studies, the mice were treated with PD98059 (5 mg/kg) or vehicle control (2% dimethyl sulfoxide) by intraperitoneal injection just prior to inoculation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation